Azathioprine in the maintainance remission in inflammatory bowel disease patients: 7-year follow up. (30th September 2020) - Cassieri, C; Mastromatteo, A M; Pica, R; Zippi, M; Corazziari, E S; Paoluzi, P; Lecca, G P; Vernia, P; Brandimarte, G; Nasi, G
Abstract: Background: Azathioprine (AZA) and thiopurine are widely used for induction and maintenance of remission in steroid dependent patients with inflammatory bowel disease (IBD). Methods: Aim of this study has been to investigate its efficacy and safety in maintaining steroid-free remission in steroid dependent IBD patients seven year after the institution of treatment. Data from consecutive IBD outpatients referred in our Institution, between 1985-2016, were reviewed and all patients treated with AZA were included in this retrospective study. AZA was administered at the recommended dose of 2-2.5 mg/kg. Results: Out of 2802 consecutive IBD outpatients visited in the index period, AZA was prescribed to 433 patients, 236 (54.5%) were affected by Crohn's disease (CD) and 197 (45.5%) by ulcerative colitis (UC). One hundred and seventy-nine patients with a follow-up < 84 months were excluded from the study. Two hundred and fifty-four patients were evaluated, 141 (55.5%) with CD and 113 (44.5%) with UC. One hundred and thirty-nine (54.7%) were male and 115 (45.3%) female (average age of 35.62 ± 14.20 SD years, range 14-74 y.). Seven year after the institution of treatment, 127 (50%) patients still were in steroid-free remission (83 CD vs 44 UC, 58.8% and 38.9%, respectively, p = 0.0024), 71 (27.9%) had a relapse requiring retreatment with steroids (29 CD vs 42 UC, 20.6% and 37.2%, respectively, p = 0.0047), 56 (22.1%) discontinued the treatment due to side effects (29 CD vs 27 UC, 20.6% and 23.9%, respectively). Loss of response from 1st to 7th year of follow-up was low, about 20%. Conclusions: Seven year after the onset of treatment 50% of patients did not require further steroid courses. After the first year loss of response was low in six subsequent years. In the present series the maintenance of steroid-free remission was significantly higher in CD than in UC patients. The occurrence of side effects leading to the withdrawal of AZA treatment has been low. Key messages: An important therapeutic moment of IBD is mantaining remission in steroid dipendent patients. AZA can be a viable and inexpensive alternative to treath these patients.